Developing Critical Thinking in Pancasila Education: The Impact of Animation-Based Video Media on Elementary Students - Made Eka Sari; I Made Tegeh; Ni Wayan Eka Widiastini (Thinking Skills and Creativity Journal, 2024)
The teaching of Pancasila Education in elementary schools still predominantly relies on conventional methods, such as lectures and textbooks, which result in low student participation and limited critical thinking and communication skills. The dominance of conventional teaching methods tends to restrict student interaction, thereby hindering the effective development of their critical reasoning and communication abilities.This study aims to develop and evaluate the effectiveness of animation-based video learning media in enhancing students' critical thinking and communication skills. The research employs a development research approach using the Research and Development (R&D) design. The study subjects consist of elementary school students who participated in Pancasila Education lessons using animation video media, with a sample size of 83 students.Data were analyzed using quantitative descriptive analysis and inferential statistical tests. The findings indicate that the use of animation-based video media enhances student engagement in learning and deepens their understanding of the subject matter. Additionally, students’ critical thinking skills showed significant improvement, as evidenced by their enhanced ability to identify, analyze, and evaluate information more effectively.